2013
DOI: 10.1152/ajprenal.00263.2013
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines as a link between obesity and chronic kidney disease

Abstract: Adipocytes secrete a number of bioactive adipokines that activate a variety of cell signaling pathways in central and peripheral tissues. Obesity is associated with the altered production of many adipokines and is linked to a number of pathologies. As an increase in body weight is directly associated with an increased risk for developing chronic kidney disease (CKD), there is significant interest in the link between obesity and renal dysfunction. Altered levels of the adipokines leptin, adiponectin, resistin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
0
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 84 publications
(174 reference statements)
1
86
0
13
Order By: Relevance
“…7 CKD is associated with an abnormal high adipokines level that may be caused by increased fat tissue production and/or reduced renal clearance of them. 8 Recent studies showed that visfatin levels are changed in CKD (DN or not) in parallel to the glomerular dysfunction, severity of proteinuria and endothelial dysfunction. [9][10][11][12] We investigated the association between visfatin levels and stages of CKD in T2DM patients with DN and the correlations with anthropometric and laboratory parameters.…”
Section: Faculdade De Farmácia Universidade Federal De Minas Geraismentioning
confidence: 99%
“…7 CKD is associated with an abnormal high adipokines level that may be caused by increased fat tissue production and/or reduced renal clearance of them. 8 Recent studies showed that visfatin levels are changed in CKD (DN or not) in parallel to the glomerular dysfunction, severity of proteinuria and endothelial dysfunction. [9][10][11][12] We investigated the association between visfatin levels and stages of CKD in T2DM patients with DN and the correlations with anthropometric and laboratory parameters.…”
Section: Faculdade De Farmácia Universidade Federal De Minas Geraismentioning
confidence: 99%
“…La exposición del glomérulo a niveles elevados de adipoquinas aumenta su permeabilidad generando hipertrofia celular con la consecuente hiperflitración (10,12,35,36). Así mismo, los adipocitos viscerales secretan angiotensinógeno, estimulando el eje renina-angiotensinaaldosterona, provocando HTA, HF y posterior ERC (36) En esta investigación se encontraron 28 (46,7%) y 24 (40%) casos de pacientes con y sin SM respectivamente con HF.…”
Section: Discussionunclassified
“…Ello es debido a que el tejido adiposo, y en especial el abdominal es considerado un órgano endocrino altamente activo que contribuye a las complicaciones renales mediante la disfunción endotelial, el estrés oxidativo y cambios en la respuesta inmune e inflamación (11), las elevaciones en los niveles de leptina, adiponectina, resistina y visfatin pueden disminuir la filtración glomerular e incremetar la albuminuria con los consecuentes cambios típicos de la enfermedad renal crónica (12).…”
Section: Introductionunclassified
“…Although the exact mechanism of adipokines' action is still unclear, they may play their role by affecting various types of cells in kidney nephrons. 6 Previous studies have shown that increased levels of leptin could lead to hypertrophy in glomerular mesangial cells that could activate fibrotic and inflammatory pathways, and also thickening of the basement membrane and consequently glomerulosclerosis. 6 Moreover, it has been demonstrated that hyperleptinemia could alter the metabolic function of proximal tubular cells and lead to tubular apoptosis.…”
mentioning
confidence: 99%
“…6 Previous studies have shown that increased levels of leptin could lead to hypertrophy in glomerular mesangial cells that could activate fibrotic and inflammatory pathways, and also thickening of the basement membrane and consequently glomerulosclerosis. 6 Moreover, it has been demonstrated that hyperleptinemia could alter the metabolic function of proximal tubular cells and lead to tubular apoptosis. 7 These structural changes in the nephrons could result in increased proteinuria, albuminuria and fibrotic pathways in tubular cells through altering the permeability of the cells.…”
mentioning
confidence: 99%